The upward accountability practices in NGO : the case of Malaysia - Noor Muafiza binti Hj. Masdar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Donors always desire information disclosure on fund management and allocation from non-governmental organizations (NGOs). However, the rights of donors in respect of their demands sometimes ignored. This phenomenon has led to the withdrawal of donor participation in NGO activities particularly where it has come to light that an NGO has misused funds. Upward accountability practices offer a way of providing information to donors in order to meet their requirements. In this study, the NGO, Aman Palestin Berhad, was investigated as a case study using a qualitative approach. The NGO manages funds mainly from Malaysian donors and distributes them to Palestinian beneficiaries. This study aims to examine the ways in which the NGO discharges accountability to its donors and to understand the reason for the selection of particular methods of accountability. The data was collected by interviewing fifteen (15) informants, observation and document analysis. Drawing on social capital theory, this study found that trustworthiness, shared norms and information channel influence the practice of upward accountability in the NGO. The findings also indicate that when either formal or informal upward accountability is used in isolation the NGO is less effective in discharging its obligations to its donors because of barriers that prevent it reaching all donors using one type of practice. Therefore, the NGO uses both formal and informal upward accountability where both of them are coexist to satisfy its stakeholders. Also, the practice of informal accountability is more dominant than formal accountability. Overall, the implementation of both types of practice enhances the NGO's ability to satisfy donors about fund management and allocation.